SOSIALISASI PENANGANAN LUKA RINGAN YANG TEPAT DI SMK PGRI 1 KOTA SERANG - Setiawati, Rini; Rahayu Prihartini, Ade; Kumalasari, Retno; Maesaroh, Maesaroh; Nugrahin, Febrina (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
This community service initiative aims to enhance students’ knowledge and skills in administering initial treatment for minor wounds through an interactive educational approach, utilizing simulation and demonstration methods. The primary participants of the program were students from SMK PGRI 1 Kota Serang, particularly those enrolled in the Mechanical Engineering and Automotive Light Vehicle Engineering programs, as they are at a higher risk of experiencing injuries. The approach involved delivering educational sessions on wound concepts, infection prevention, and wound care techniques, followed by practical sessions using basic first aid equipment. The outcomes of the activity indicated a significant improvement in students’ understanding, attitudes, and competencies in wound management. Participants demonstrated strong enthusiasm, engaged actively in discussions, and successfully applied proper wound care techniques during practice sessions. self-reliance in treating minor wounds appropriately and preventing potential complications